Dynamic methods and process advancements in mechanical, manufacturing, and materials engineering - Davim, J. Paulo (Engineering Science Reference, 2013)
"This book examines the theoretical foundations of new generation graphical design methods, models, and tools to facilitate reasoning on compositions of systems and services across organizational and technical system boundaries."--Provided by publisher.